Engineering three-dimensional microenvironments towards in vitro disease models of the central nervous system. (6th June 2019) - Yildirimer, Lara; Zhang, Qiang; Kuang, Shifeng; Cheung, Chung-Wai James; Chu, Kyle Alexander; He, Yong; Yang, Mo; Zhao, Xin
Abstract: The central nervous system (CNS) has a highly complex biophysical and biochemical environment. Despite decades of intensive research, it is still an enormous challenge to restore its functions and regenerate lost or damaged CNS tissues. Current treatment strategies remain sub-optimal because of (1) the hostile microenvironment created post CNS injury, and (2) insufficient understanding of the pathophysiology of acute and chronic CNS diseases. Two-dimensional (2D) in vitro models have provided tremendous insights into a wide range of cellular interactions. However, they fail to recapitulate the complex cellular, topographical, biochemical, and mechanical stimuli found within the natural three-dimensional (3D) CNS. Also, the growing ethical needs to use fewer animals for research further necessitates 3D in vitro models to mimic all or part of the CNS. In this review, we critically appraise the status quo and design considerations of 3D in vitro neural disease and injury models that resemble in vivo conditions. This review mainly focuses on the most recent advances in tissue engineering techniques such as microfluidics, organs-on-a-chip and stem cell technology. Furthermore, we review recent models aiming to elucidate the underlying pathophysiology of CNS diseases. If armed with deeper understanding, it will be possible to develop high-throughput drug screening platforms and new treatments for CNS diseases and injuries.